Carbon Dioxide Emissions Intensity Convergence: Evidence From Central American Countries - Apergis, Nicholas; Payne, James E.; Rayos-Velazquez, Marco (Frontiers in Energy Research, 2020)
This paper extends the literature on the convergence of carbon dioxide emissions intensity and its determinants (energy intensity and the carbonization index) for six Central American countries over the period 1971 to 2014. Using the Phillips-Sul club convergence approach, the results indicate two distinct convergence clubs with respect to carbon dioxide emissions intensity and energy intensity with the first convergence club consisting of Costa Rica, El Salvador, Guatemala, and Honduras and the second convergence club consisting of Nicaragua and Panama. However, in the case of the carbonization index, only one convergence club emerges that includes Costa Rica, El Salvador, Guatemala, Honduras, and Nicaragua with Panama exhibiting non-convergent behavior.